Genetic Differentiation of Brown Planthopper Nilaparvata lugens (StÃ¥l) Populations in Asia: Genetic Differentiation of Brown Planthopper in Asia - Bagyo Yanuwiadi; Rahmat Grahadi (Journal of Tropical Life Science, 2022)
Brown Planthopper is one of the economically important rice pests that cause several crop failures in Asian countries. Unfortunately, Brown Planthopper could migrate to neighboring countries to generate interpopulation breeding, thus further increasing the gene flow and spreading insecticide resistance. This research aimed to understand the genetic differentiation of Brown Planthopper among all Asian populations. This study used two COI sequences from Malang, Indonesia, and 25 sequences from GenBank to analyze the genetic structure with phylogenetic tree and haplotype network. The uncorrected pairwise distance result showed that the Brown Planthopper population in Asia has a relatively low genetic distance. We also found that the Brown Planthopper population was clustered based on the geographical region of South Asia, East Asia-Mainland South East Asia, and Indonesia. Thus, we concluded that the migration of Brown Planthopper was limited to East Asia and Mainland South East Asia only. Further studies are needed to confirm the migration route of Brown Planthopper in South Asia and Southeast AsiaKeywords: BPH, Genetic differentiation, Haplotype network, Phylogenetic